2015
DOI: 10.5897/ajb2015.14508
|View full text |Cite
|
Sign up to set email alerts
|

Application of biofilms in the post-harvest conservation of pequi (Caryocar brasiliense Camb.)

Abstract: Pequi (Caryocar Brasiliense Camb.), fruit characteristic of the Brazilian cerrado, has sensory and nutritional characteristics, pleasant flavor and aroma and considerable presence of lipids and fiber, essential for human consumption. The aim of this study was to assess the post-harvest conservation of this fruit by using different sources of biofilms as a means to ensure the maintenance of fruit physical and chemical characteristics in order to increase its shelf life. Fruits were submitted to four treatments:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…According to Han and Gennadios, 2005, the edible coatings can protect fruits and vegetables from dehydration due to their moisture barrier property, resulting in an extension of the shelf life of minimally processed products. But, Placido et al, (2015) concluded that, in pequi fruit, the vitamin C, titratable acidity, soluble solids contents and weight loss showed that starchbased coatings did not achieve satisfactory results. Despite these results, it was found in the present study that the tapioca-starch based coatings reduced weight loss in the case of fresh-cut cauliflower.…”
Section: Rd International Symposium For Agriculture and Food -Isaf 20...mentioning
confidence: 99%
“…According to Han and Gennadios, 2005, the edible coatings can protect fruits and vegetables from dehydration due to their moisture barrier property, resulting in an extension of the shelf life of minimally processed products. But, Placido et al, (2015) concluded that, in pequi fruit, the vitamin C, titratable acidity, soluble solids contents and weight loss showed that starchbased coatings did not achieve satisfactory results. Despite these results, it was found in the present study that the tapioca-starch based coatings reduced weight loss in the case of fresh-cut cauliflower.…”
Section: Rd International Symposium For Agriculture and Food -Isaf 20...mentioning
confidence: 99%
“…Cassava starch is produced in large scale in Brazil and presents good characteristics for the formation of resistant and transparent films, being efficient barrier for water loss, giving good appearance and intense brightness to the fruit. In addition, It is edible and present low price when compared to the other commercial waxes [13,14].…”
Section: Introductionmentioning
confidence: 99%